2021
DOI: 10.1007/s13204-021-01798-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of amine-functionalized graphene oxide by ultrasound-assisted reactions and density functional theory mechanistic insight

Abstract: Herein described is a facile preparation protocol by which amino-alcohol derivatives of graphene oxide (GO) can be conveniently synthesized in high yield and a short time by an ultrasound treatment of ethanol-graphite-oxide suspensions and amines. Linear primary amines of different chain length rapidly react with graphite oxides prepared from powder and flakes, leading to the formation of GO amino-alcohol derivatives. Characterization of the amine-modified materials by XRD, TGA, FTIR, and Raman demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 110 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…To synthesize amine-functionalized GCN, a reported method with some modifications was followed . The NH 2 –GCN was prepared using butylamine as a precursor.…”
Section: Methodsmentioning
confidence: 99%
“…To synthesize amine-functionalized GCN, a reported method with some modifications was followed . The NH 2 –GCN was prepared using butylamine as a precursor.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal stability of the catalyst was examined using TGA, as shown in Figure 1 (d) and it was observed that the thermal stability of GCN was less than that of NH2-GCN, due to its surface functionalization. 23 A weight loss of 4.6 % was observed for GCN up to 450 o C and for NH2-GCN it was about 2.4 % up to 450 o C. This weight loss, up to 160 o C, is due to the absorbed water molecules in the nanosheets. This loss is less in the case of NH2-GCN due to less absorption of water molecules because of increased hydrophobicity.…”
Section: Scheme 1 Schematic Representation Of Synthesis Of Nh2-gcn Na...mentioning
confidence: 92%
“…This loss is less in the case of NH2-GCN due to less absorption of water molecules because of increased hydrophobicity. 23,39 The second weight loss observed between 200 -400 o C for NH2-GCN is very less whereas, in the case of GCN, the second weight loss is more due to disintegration of -NH2 group. Furthermore, in the range of 450 -650 o C, complete decomposition of the C-N network of the heptazine ring occurs in both, GCN and NH2-GCN.…”
Section: Scheme 1 Schematic Representation Of Synthesis Of Nh2-gcn Na...mentioning
confidence: 98%
See 1 more Smart Citation
“…An interesting study was performed by Shen B. et al where the functionalization was achieved solely by ultrasonication on the aqueous mixture of pristine graphene and PVA with the estimated content of PVA on graphene to be approximately 35 % [39] . In addition, ultrasound-assisted direct functionalization of GO with nitrogen [40] , 5-aminoindazole [41] , and amino-alcohol [42] were recently presented. However, most of the studies lack of systematic approach on how to control the degree of functionalization by controlling ultrasound parameters.…”
Section: Introductionmentioning
confidence: 99%